1998
DOI: 10.2527/1998.7651488x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy source and escape protein on receiving and finishing performance and health of calves.

Abstract: Two receiving and two finishing trials evaluated energy source and escape protein supplementation for calves. In receiving Trial 1, 398 calves (257 ± 24 kg BW) were used in a 2 × 2 factorial arrangement of treatments. Energy sources were dryrolled corn (DRC) and wet corn gluten feed (WCGF); each was fed without or with supplemental escape protein (EP). Calves fed WCGF gained slower ( P < .05) and consumed less DM ( P < .01) than calves fed DRC. Feed efficiency improved ( P < .10) with EP supplementation. In fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
1
7
2
4
Order By: Relevance
“…No differences (P > 0.10) were noted among treatments for ADG during days 0 to 14, 15 to 28, or for the 28-d receiving period. This agrees with results of McCoy et al (1998), who observed that ADG by newly received calves were not affected by protein supplement. No differences (P > 0.10) were noted in DMI of hay for days 0 to 14, or DMI for the overall 28-d receiving period.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…No differences (P > 0.10) were noted among treatments for ADG during days 0 to 14, 15 to 28, or for the 28-d receiving period. This agrees with results of McCoy et al (1998), who observed that ADG by newly received calves were not affected by protein supplement. No differences (P > 0.10) were noted in DMI of hay for days 0 to 14, or DMI for the overall 28-d receiving period.…”
Section: Methodssupporting
confidence: 83%
“…ed) during the experiment (Table 3). In contrast, McCoy et al (1998) reported a negative correlation between metabolizable protein supply and morbidity, indicating that increased metabolizable protein supply might improve health. Our data suggest that dietary urea concentration up to 1% DM in a 14% CP diet (steam-flaked corn based) has no affect on BRD morbidity.…”
Section: Methodsmentioning
confidence: 82%
“…Quanto à utilização de fontes ou níveis protéicos, os resultados observados têm sido discretos ou mesmo ausentes (SINDT et al, 1993;SHAIN et al, 1998;McCOY et al, 1998).…”
Section: Rev Bras Zootec 30(5):1590-1599 2001unclassified
“…Além disso, o farelo de soja pode aumentar o fornecimento de proteína metabolizável não só através do maior fluxo de proteína microbiana como pelo aporte de proteína não degradável no rúmen ao intestino (MILTON et al, 1997b Entretanto nas 11 comparações (SINDT et al, 1993 a,b;CECAVA et al, 1994;CAMPBELL et al, 1997;BARAJAS E ZINN, 1998;McCOY et al, 1998;DUT et al, 2003;GLEGHORN et al, 2004) A eficiência alimentar (GPD/CMS) dos animais alimentados com milho (0,153) foi similar (P>0,05) à dos animais alimentados com sorgo (0,146). Estes dados não estão de acordo com os dados da revisão de SANTOS et al (2004).…”
Section: Coleta De Dados De Espessura De Gorduraunclassified
“…Nas 11 comparações (SINDT et al, 1993a,b;CECAVA et al, 1994;CAMPBELL et al, 1997;BARAJAS E ZINN, 1998;McCOY et al, 1998;DUT et al, 2003;GLEGHORN et al, 2004) entre proteína verdadeira e uréia para bovinos em terminação, compiladas por SANTOS (2005), com rações ricas em milho ou sorgo, diferentemente deste experimento, a eficiência alimentar (GPD/CMS) não diferiu em 10 comparações. A eficiência (GPD/CMS) foi de 0,161 nos tratamentos com a uréia contra 0,158 com proteína verdadeira.…”
Section: Coleta De Dados De Espessura De Gorduraunclassified